Deformation and failure of sugarcane bagasse reinforced PP. (March 2019) - Anggono, Juliana; Farkas, Ágnes Elvira; Bartos, András; Móczó, János; Antoni,; Purwaningsih, Hariyati; Pukánszky, Béla
Graphical abstract: Highlights: PP/sugarcane bagasse composites were prepared from agricultural waste. Sugarcane bagasse fibers reinforce polypropylene similarly to other natural fibers. Debonding dominates when adhesion is weak, while fracture occurs when it is strong. Increased plastic deformation results in slightly improved impact resistance. Abstract: Polypropylene composites were prepared from sugarcane bagasse fibers by extrusion and injection molding. Wood flour was used as reference filler in the study. The fiber content of the composites changed between 0 and 30 wt% in 5 wt% steps. Maleated polypropylene was used as coupling agent to improve interfacial adhesion. Mechanical properties were characterized by tensile and fracture testing, while local deformation processes were followed by acoustic emission and instrumented impact testing, as well as by the analysis of scanning electron micrographs. The results showed that sugarcane bagasse fibers reinforce polypropylene similarly to other natural fibers. They increases stiffness, but decrease tensile yield stress, tensile strength and deformability. Increased interfacial adhesion leads to the considerable improvement of reinforcement. Bagasse fiber and wood flour filled composites have very similar properties. The impact resistance of the composites increased in the presence of both fibers compared to the neat matrix. Debonding is the dominating process in the absence of the coupling agent, while mainly fiber fracture occurs in its presence. Increased plastic deformation after debonding results in slightly improved impact resistance.